Applying design for six sigma to software and hardware systems - Maass, Eric.; McNair, Patricia D. (Upper Saddle River, NJ : Prentice Hall, 2010)
Design for Six Sigma (DFSS) offers engineers powerful opportunities to develop more successful systems, software, hardware, and processes. In Applying Design for Six Sigma to Software and Hardware Systems, two leading experts offer a realistic, step-by-step process for succeeding with DFSS. Their clear, start-to-finish roadmap is designed for successfully developing complex high-technology products and systems that require both software and hardware development.
Chapter 1: Introduction: History and Overview of DFSS -- Chapter 2: DFSS Deployment -- Chapter 3: Governance, Success Metrics, Risks, and Certification -- Chapter 4: Overview of DFSS Phases -- Chapter 5: Portfolio Decision Making and Business Case Risk -- Chapter 6: Project Schedule Risk -- Chapter 7: Gathering Voice of the Customer to Prioritize Technical Requirements -- Chapter 8: Concept Generation and Selection -- Chapter 9: Identification of Critical Parameters and FMEA -- Chapter 10: Requirements Flow-Down -- Chapter 11: Software DFSS and AgileChapter 12: Software Architecture Decisions -- Chapter 13: Predictive Engineering: Continuous and Discrete Transfer Functions -- Chapter 14: Predictive Engineering: Optimization and Critical Parameter Flow-Up -- Chapter 15: Predictive Engineering: Software Optimization -- Chapter 16: Verification of Design Capability: Hardware -- Chapter 17: Verification of Reliability and Availability -- Chapter 18: Verification: Software Testing Combined with DFSS Techniques -- Chapter 19: Verification of Supply Chain Readiness -- Chapter 20: Summary and Future Directions.
Includes bibliographical references and index.
1
Keywords: New products; Six sigma (Quality control standard)